Development and validation of a food frequency questionnaire for Japanese athletes (FFQJA). Issue 1 (10th May 2021) - Ishikawa-Takata, Kazuko; Okamoto, Kaori; Taguchi, Motoko
Abstract: Background: Food frequency questionnaires are considered an effective method for assessing habitual dietary intake, but they must be developed or validated with the target population. Portion size, supplement use and food choice are thought to be especially important methodological considerations for assessing athletes' dietary intake. This study aimed to develop and validate a food frequency questionnaire for Japanese athletes using data from this population. Methods: We used dietary records from 440 Japanese athletes involved in our previous projects. Food items were analyzed using cumulative percentage contributions and multiple regression analysis, to give a selection of 62 basic food items and four supplemental items. The validity of the questionnaire was evaluated among another 77 Japanese athletes by comparing nutrient intakes assessed using the questionnaire with dietary records. Reproducibility was evaluated by comparing a second questionnaire completed 2–3 weeks later by 36 of the athletes in the validation study. Validity was assessed using crude Spearman's correlation coefficients (CCs), energy-adjusted CCs, intraclass CCs (ICCs), and Kappa index values. Reproducibility was assessed by CCs, energy-adjusted CCs, and ICCs. Results: In the validation analysis, the median crude CC for all of the nutrients was 0.407, ranging from 0.222 for dietary fiber to 0.550 for carbohydrate. The median energy-adjusted CC was 0.478, and the median ICC was 0.369. When we divided the athletes into quartiles, 65% (vitamin B1 ) to 86% (iron) of athletes were classified into the same or adjacent categories using the questionnaire and dietary records, with a median Kappa statistic of 0.32. In the reproducibility analysis, the median crude CC between the two completed questionnaires was 0.654, ranging from 0.582 (carbohydrate) to 0.743 (vitamin B2 ). The median energy-adjusted CC was 0.643, and the median ICC was 0.647. Conclusions: The new 62-item food frequency questionnaire is both reliable and valid and may be useful for assessing food intake in Japanese athletes.